FAKTOR-FAKTOR YANG MEMPENGARUHI PELUANG TENAGA KERJA SUMATERA BARAT MELAKUKAN MIGRASI ULANG ALIK - Ilham Utama Putra; Alpon Satrianto (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to find out effect of  wage level, education level, age, gender, and marital status on the opportunities of West Sumatera worker to migrate commuter. This type of research is descriptive and associative. The type of data is secondary. This study uses the National Labor Force Survey data in 2017 and using logistic regression analysis with the number of respondents as many as 6.560 people. The result of this study indicate that : (1) Wage rates have a positive and significant effect on the opportunities of West Sumatra workers to migrate commuter, (2) Educational level has a positive and significant effect on the opportunities of West Sumatra workers to migrate commuter, (3) Age positive and not significant effect on the opportunities of West Sumatra workers to migrate commuter, (4) Gender has a positive and significant effect on the opportunities of West Sumatra workers to migrate commuter, (5) Marital status has a positive and not significant effect on employment opportunities West Sumatra to migrate commuter. (6) employment sector has a positive and significant effect on employment opportunities west Sumatra to migrate commuter.